Peran Kepolisian dalam Menanggulangi Penyebaran Berita Bohong (Hoax) - Kalvin Koyomi Rumbewas (Kyadiren, 2022)
This study aims to examine the role of Biak’s Resort Police in tackling the spread of fake news (hoax) and examine the various obstacles faced in tackling the spread of the hoax. This research was empirical juridical research. The results showed that Biak’s Resort Police had made efforts in the form of penal and non-penal in tackling fake news (hoax). The penal effort is implemented through law enforcement for people who clearly have spread the hoax. The non-penal efforts include counseling and providing understanding regarding the dangers of hoax. In addition, Various factors hinder law enforcement by officials in eliminating hoax, namely factors such as punishment, facilities, law enforcement and community culture.